The Association Between Generalized and Specific Problematic Internet Use and Its Gender Differences Across Different Educational Levels - Tian, Yu; Zuo, Tengfei; Sun, Qianqian; Sun, Lu; Cao, Sheng; Qin, Ningbo (Frontiers in Psychology, 2021)
This study had two aims: to test the effect and effect size of specific problematic Internet use (SPIU; online shopping, online pornography, social network site (SNS) usage, and Internet gaming) on generalized problematic Internet use (GPIU); to reveal the gender differences in GPIU and SPIU for students from the elementary school level to the university level. In total, 5215 Chinese students (2303 male, mean age = 16.20 years; ranging from 10 to 23 years) from 4 types of schools (elementary school, junior high school, senior high school, and university) provided self-report data on demographic variables (gender, and study period), online shopping, online pornography, SNS usage, Internet gaming, and GPIU. After calculations had been controlled for demographic variables, the results indicated that (i) online shopping, online pornography, SNS usage, and Internet gaming positively predicted GPIU; and Internet gaming was the most critical predictor of GPIU. (ii) for elementary school, gender difference was revealed in Internet gaming and GPIU; for junior high school, gender difference was revealed in online shopping, online pornography, Internet gaming, and GPIU; for senior high school, gender difference was revealed in online shopping, online pornography and Internet gaming; for university, gender difference was revealed in online shopping, SNS usage, online pornography, Internet gaming and GPIU. These results provided us a further understanding of the association between GPIU and SPIU, and gender difference in PIU.